Interactive effects of seasonal-demand characteristics on manufacturing systems. Issue 10 (18th May 2016) - Bhat, Sanket; Krishnamurthy, Ananth
Abstract : In this paper, we identify different characteristics of seasonal demands and analyse their impact on manufacturing systems. In particular, we consider a single-stage production facility that has flexibility to adjust its production rates or inventory target levels. Using Markov decision process formulation, we analyse a model that minimises the total cost under infinite horizon discounted and average cost criteria. Through extensive numerical studies, we reveal several insights related to the individual and joint impact of seasonal demand characteristics that are of practical interests to manufacturers.